2018
DOI: 10.1108/ijoem-04-2017-0113
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of crisis signals across the world: evidence from subprime crisis of 2008-2009

Abstract: Purpose The innovations in fundamentals coupled with noise traders induce co-movement in diverse markets. This co-movement in equity markets which is evidenced higher during the turmoil period influences economic fundamentals of a country dissimilar in nature. The purpose of this paper is to examine whether economic fundamentals or investors’ behavior attributable to disturbances across the world are the rationale behind the crisis transmission, and thereby distinguish fundamental-based contagion from investor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 89 publications
0
8
0
1
Order By: Relevance
“…In addition, therefore Islamic financial literacy has a strong relationship with AIB, and IFL also encourages individuals to take part in risky investments. (Rajan and Santhakumar, 2018). Therefore, a Hypothesis was developed: H1 High IFL positively affects the AIB.…”
Section: Islamic Financial Literacy (Ifl)mentioning
confidence: 99%
“…In addition, therefore Islamic financial literacy has a strong relationship with AIB, and IFL also encourages individuals to take part in risky investments. (Rajan and Santhakumar, 2018). Therefore, a Hypothesis was developed: H1 High IFL positively affects the AIB.…”
Section: Islamic Financial Literacy (Ifl)mentioning
confidence: 99%
“…For example, previous research has found that risk avoidance is correlated with religiosity (Breuer, Riesener & Salzmann 2014). Therefore, the stability of a high level of Islamic financial literacy will encourage individuals to make wise decisions (Rajan & Santhakumar 2018). This survey on Islamic banking knowledge found that while nearly all Muslims are only 27.3 percent of those who are aware of Islamic banks actually understand the differences between Islamic and conventional banks (Hamid & Nordin 2001;Bley & Kuehn 2004).…”
mentioning
confidence: 91%
“…Thus, investors change their expectations and transmit the shock through a propagation mechanism that does not exist during stable periods. Testing the propagation of shocks, Rajan and Santhakumar (2018) found that investors have induced contagion. Javaira and Hassan (2015) indicated the presence of a herding behavior among investors during the liquidity crisis in the Pakistani stock market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, the herding behavior of investors during a context of information asymmetry induces markets to move together. Rajan and Santhakumar (2018) found that investors induce contagion in the crisis period. As a matter of fact, in this context, we consider the behavioral theory of contagion, referring to the investor's sentiment.…”
Section: Introductionmentioning
confidence: 99%